Найдите значение выражения: 36 × 6⁻³ + 216 × 6⁻² + 2 × 6⁻¹

sernikovs sernikovs    2   07.09.2019 05:50    0

Ответы
j5022778 j5022778  06.10.2020 22:32
36*6^-3+216*6^-2+2*6^-1=36* \frac{1}{216} +216* \frac{1}{36} +2* \frac{1}{6} = \frac{1}{6}+6+ \frac{1}{3}= \frac{1+36+2}{6} = \frac{39}{6}= \frac{13}{2} =6,5
ПОКАЗАТЬ ОТВЕТЫ
Макоська Макоська  06.10.2020 22:32
=(36+216×6+2×6²)×6-³ = (36+1296+2×36)×6-³ = (36+1296+76)×6-³ = 1404×6-³ = 39×6²×6-³ = 39×6-¹
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра